Econometric Measurement of the Relationship between Tourism Revenues and Economic Growth. Study Case of Kazakhstan and Kyrgyzstan - HUSEYNLI, Nigar (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).19, 2022)
The purpose of this research is to establish the link between Kazakhstan's and Kyrgyzstan's international tourist income and economic development from 1998 to 2019. The Linear Regression Model was used to see whether there was a significant link between the dependent and independent variables, as well as how the variables influenced economic growth. The World Bank provided the data for the research, which included yearly data. A set of assumption tests were performed throughout the analytical phase to determine the model's relevance. The logarithm of the dependent variable was used to create the model. The inflation factors of variance (WIF) test were used to determine if the independent variables were unrelated to one another. Another assumption was used to determine the normal distribution of error terms: the Shapiro-Wilk W test. A positive linear association was found between economic development and foreign tourist revenues in the nations studied, according to the results of a series of assumption tests and regression analysis. According to the results of the most recent regression study, the variables in both nations have a positive linear connection.